Synthesis and Structure of Novel Anhydrogalactosucrose Derivative - Zhang1, Jingyu; Wang2, Qinglong; Hou2, Xuehui (Asian Journal of Chemistry, 2014)
A novel anhydrogalactosucrose derivative was prepared from sucrose. Its structure was determined by single crystal X-ray diffraction analysis. The crystals are monoclinic, space group P21 with a = 5.40373(15), b = 18.3877(5), c = 7.68465(19) Å, a = 90.00, b = 103.299(3), g = 90.00°, V = 743.08(4) Å3, Z = 2, F(000) = 376.0, Dc = 1.614g/cm3, μ = 4.307 mm-1, the final R = 0.0344 and wR = 0.0881. A total of 6472 reflections were collected, of which 2732 were independent (Rint = 0.0286).